PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP DISIPLIN KARYAWAN DAN DOSEN DI SEKOLAH TINGGI ILMU KESEHATAN (STIKES) ABDI NUSA PANGKALPINANG - Susanto, Dedi; Burhanuddin, Burhanuddin (ECONOS Jurnal Ekonomi dan Sosial, 2019)
Higher education has an important role in producing quality human resources. In order to be able to carry out its role well, universities are required to be able to implement good human resource management, especially in improving the performance of employees and lecturers. This study was intended to analyze the effect of motivation and compensation on the discipline of employees and lecturers at the Abdi Nusa Pangkalpinang School of Health Sciences. The population and sample are all employees and lecturers totaling 52 people. Measurement of research variables with instruments in questionnaires quantified with a Likert scale. The method of analysis uses multiple regression analysis. Hypothesis testing uses t-test.  The results of this study result that the motivation and compensation respectively partially have a positive and significant effect on the discipline of employees and lecturers at the Abdi Nusa Pangkalpinang School of Health Sciences. The recommendation of this research is that the institution is expected to provide support and awards to improve the performance of employees and lecturers.